Exploring the mediating roles of sport commitment and resilience between life satisfaction and social anxiety among Chinese primary school students - Kan, Wencong; Xu, Menglin; Wang, Yufen; Zuo, Changhui; Yi, Lei; Dong, Xiaoxi (Frontiers in Psychology, 2025)
BackgroundThe mental health of children and adolescents has become urgent global concerns, particularly in China, where intense academic competition, societal pressures, and fast-paced lifestyles exacerbate psychological challenges. These factors significantly hinder healthy psychological development, underscoring the need for innovative approaches to address youth subjective wellbeing. This study investigates the mediating roles of resilience and sport commitment in the relationship between social anxiety and life satisfaction.MethodsA cross-sectional design was employed, involving 948 primary school students (446 females, 502 males) from four major Chinese cities. Participants completed an online survey assessing sport commitment, life satisfaction, resilience (personal and caregiver-related), and social anxiety. Path analysis using a maximum likelihood estimator was conducted to examine the mediating roles of sport commitment, personal resilience, and caregiver resilience in the relationship between social anxiety and life satisfaction. Indirect effects were evaluated using bootstrap sampling with a bias-corrected 95% confidence interval.ResultsThe findings revealed a satisfactory model fit, χ2(5) = 8.414, p = 0.135, CFI = 0.998, TLI = 0.992, RMSEA = 0.027, 90% CI = (0.000, 0.057), and SRMR = 0.018, with 36.4% of the variation in life satisfaction that could be explained by the model. Specifically, sport commitment, personal resilience, and caregiver resilience significantly mediated the relationship between social anxiety and life satisfaction. The total indirect effect was significant, accounting for 67.93% of the total effect. In addition, social anxiety was negatively associated with life satisfaction.ConclusionThis study advances the literature by highlighting the protective roles of resilience and sport commitment in mitigating the impact of social anxiety on life satisfaction. It underscores the importance of fostering resilience at individual, familial, and societal levels and emphasizes the role of educational systems in promoting youth subjective well-being. Practical implications include integrating sport-based activities and resilience-building programs into school curricula, as well as fostering collaboration among parents, educators, and community stakeholders. Future research should explore targeted intervention strategies and their long-term impacts on youth subjective wellbeing.